Kajian Penambahan Kapur dan Serbuk Marmer Terhadap Kuat Tekan Tanah Lempung - Waruwu, Aazokhi; Priyo, Aaron Nicholas; Raymond, Raymond (MEDIA KOMUNIKASI TEKNIK SIPIL, 2024)
The design of roads and other constructions requires attention to the subgrade. In Indonesia, clay soils are quite common and tend to have low bearing capacity. To increase the bearing capacity of clay soils, it is necessary to carry out soil improvement and stabilization measures. Soil stabilization can be done by adding stabilizing materials such as lime and marble powder. Before stabilizing the soil, it is necessary to test soil characteristics such as testing water content, unit weight, Atterberg limit, specific gravity, sieve analysis and hydrometer. This research was carried out to obtain the most optimum composition of the stabilization mixture. This research used lime additives with compositions of 1.5% and 3%, respectively, marble powder was added with compositions of 3%, 6% and 9%. After that, a compaction test is carried out to determine the optimum water content and maximum dry weight. After getting the results from the compaction test, the soil bearing capacity can be analyzed using the Unconfined Compression Test. The test results showed that the addition of 3% lime and 9% marble powder resulted in a significant increase in compressive strength and shear strength values in clay soil. Closed-molded test specimens show an increasing trend in compressive strength values better than open-molded specimens.